Coulomb enhancement of superconducting pair-pair correlations in a 3 4-filled model for k-(BEDT-TTF)2X - De Silva, W.W.; Gomes, N.; Mazumdar, S.; Clay, R.T. (Physical Review, 2016)
Attached

We present the results o f precise correlated-electron calculations on the monomer lattices o f the organic chaige-transfer solids k -(B ED T -T T F)2X for 32 and 64 molecular sites. Our calculations are for band parameters corresponding to X = Cu[N (C N )2]CI and Cu2(C N )3, which are semiconducting antiferromagnetic and quantum spin liquid, respectively, at ambient pressure. We have performed our calculations for variable electron densities p per B E D T -T T F molecule, with p ranging from I to 2. We find that d-wave superconducting pair-pair correlations are enhanced by electron-electron interactions only for a narrow carrier concentration about p = 1.5, which is precisely the carrier concentration where superconductivity in the charge-transfer solids occurs. Our results indicate that the enhancement in pair-pair correlations is not related to antiferromagnetic order, but to a proximate hidden spin-singlet state that manifests itself as a charge-ordered state in other charge-transfer solids. Long-range superconducting order does not appear to be present in the purely electronic model, suggesting that electronphonon interactions also must play a role in a complete theory o f superconductivity.